Effects Of Internet-Based Social NetworkAmong University Students’ Academic Performance: A Case Study In School Of Quantitative Sciences - Ahmad, Farah (Indonesian Journal of Education Methods Development, 2019)
This paper is to investigate the effect of google usage on uumsqs final yearstudents’ academic performance. The scope of this paper is focusing on studying the effects of google usage on university utaramalaysia (uum) students’ academic performance. This study has been carried out among final year students of school of quantitative science (sqs) by did survey through asking respondents for information using written questioning which is questionnaire. The survey from the respondents takes time almost a week. It is believe that google usage will create a positive impact on students. By doing this study, students can know whether google is affecting their academic performance. The sources where students refer for academic purpose can also been seen. Besides, the role of google that can help students to gain extra knowledge in the learning process can be identify. Students can find out more advantages that is brought by google which can leave a positive effect on their academic performance.